The assisted reproductive technology subsidy in Korea: criticism from a perspective of reproductive responsibility - Junga Kim, Claire (Acta Bioethica, 2018)
The Korean government’s new policy of subsidizing assisted reproductive technology (ART) fees to increase the birth rate reflects a lack of concern for future generations and their quality of life. It seems wrong to treat the future child as just a number that contributes to achieving the target birth rate, or as a mere means of solving a problem facing the current generation. However, when one tries to articulate the shortcomings of this new policy, one realizes that the ontological arguments surrounding this issue, namely the non-identity problem is complex. I propose the concept of reproductive responsibility as a response to the possible life. This concept presupposes a relationship between the reproductive agent and the possible new life. Since the concept draws the normative standard from that relationship, it resolves the non-identity problem and makes it possible to criticize the new policy of subsidizing ART.